DETERMINATION OF ACCELERATED FACTORS IN GRADIENT DESCENT ITERATIONS BASED ON TAYLOR’S SERIES - Petrović, Milena; Kontrec, Nataša; Panić, Stefan (Bulletin of Natural Sciences Research, 2017)
In this paper the efficiency of accelerated gradient descent methods regarding the way of determination of accelerated factor is considered. Due to the previous researches we assert that the use of Taylor’s series of posed gradient descent iteration in calculation of accelerated parameter gives better final results than some other choices. We give a comparative analysis of efficiency of several methods with different approaches in obtaining accelerated parameter. According to the achieved results of numerical experiments we make a conclusion about the one of the most optimal way in defining accelerated parameter in accelerated gradient descent schemes.